The Performance and Signalling Process of Initial Public Offers in Malaysia: 1980-1996 - Md. Nassir, Annuar; Mohamad, Shamsher (Universiti Putra Malaysia Press, 1998)
Malaysian IPOs are, on average, substantially underpriced compared to underpricing in other emerging and developed market. The findings of this study suggest that this average abnormal return on the first trading day is 135 percent, after which the returns decline slightly in the first week and gradually increase thereafter. A test on possible signalling attributes of new issues to potential investors reveal that of all the suggested determinants, the ex-ante risk factor seems to explain the level of underpricing.